Directing the Breathing Behavior of Pillared-Layered Metal Organic Frameworks via a Systematic Library of Functionalized Linkers Bearing Flexible Substituents - Henke, Sebastian; Schneemann, Andreas; Wuetscher, Annika; Fischer, Roland A. (Journal of the American Chemical Society, 2012)
Flexible metal organic frameworks (MOFs), also referred to as soft porous crystals (SPCs), show reversible structural transitions dependent on the nature and quantity of adsorbed guest molecules. In recent studies it has been reported that covalent fiinctionalization of the organic linker can influence or even integrate framework flexibility ("breathing") in MOFs. However, rational fine-tuning of such responsive properties is very desirable but challenging as well. Here we present a powerful approach for the targeted manipulation of responsiveness and framework flexibility of an important family of pillared-layered MOFs based on the parent structure [Zn-2(bdc)(2)(dabco)1 (bdc = 1,4-benzenedicarboxylate; dabco = 1,4-diazabicyclo[2.2.2]octane). A library of functionalized bdc-type linkers (fu-bdc), which bear additional dangling side groups at different positions of the benzene core (alkoxy groups of varying chain length with diverse functionalities and polarity), was generated. Synthesis of the materials [Zn-2(fu-bdc)(2)(dabco)](n) yields the respective collection of highly responsive MOFs. The parent MOF is only weakly flexible; however, the substituted frameworks of [Zn-2(fu-bdc)(2)(dabco)](n) contract drastically upon guest removal and expand again upon adsorption of DMF (N,N-dimethylformamide), EtOH, or CO2, etc., while N-2 is hardly adsorbed and does not open the narrow-pored form. These "breathing" dynamics are attributed to the dangling side chains that act as immobilized "guests", which interact with mobile guest molecules as well as with themselves and with the framework backbone. The structural details of the guest-free, contracted form and the gas sorption behavior (phase transition pressure, hysteresis loop) are highly dependent on the nature of the substituent at the linker and can therefore be adjusted using our approach. Combining our library of functionalized linkers with the concept of mixed-component MOFs (solid solutions) offers very rich additional dimensions of tailoring the structural dynamics and responsiveness. Implementation of two differently functionalized linkers in varying ratios yields multicomponent single-phased [Zn-2(fu-bdc')(2x)(fu-bdc")(2-2x)(dabco)](n) MOFs (O < x < 1) of increased inherent complexity, which feature a non-linear dependence of their gas sorption properties on the applied ratio of components. Hence, the responsive behavior of such pillared-layered MOFs can be extensively tuned via an intelligent combination of functionalized linkers.